A Leprosy patient who was abandoned by his friends, family and society - Habib, A (Bangladesh Medical Journal, 2014)
DOI: http://dx.doi.org/10.3329/bmj.v42i2.18990 Bangladesh Med J. 2013 May; 42 (2): 70